Implementation of Digitization Audit Reporting for Supports Performance LPSQ Function at PT.XXX - Sari, Latifa Ika; Syauvika, Aurendya Bulan Farah (RSF Conference Series: Engineering and Technology, 2023)
Loss Prevention Safety and Quality/Designed Person Ashore (LPSQ/DPA) is responsible for ensuring safety elements on Pertamina International Shipping vessels and ensuring the fulfillment of maritime-worthy documents before ships set sail. This research aims to identify the challenges faced by PT.XXX in implementing digital audit reporting to support the performance of the LPSQ Function and to determine the benefits of implementing digital audit reporting on the performance of the LPSQ Function at PT.XXX. The research method used in this study is a qualitative descriptive approach. Data collection techniques include interviews with internal and external sources, observations, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing research conclusions. Data validity testing includes credibility testing, source and technique triangulation, and member checking. This research reveals several challenges in the data grouping process, human errors, and server downtime. The benefits of implementing digital audit reporting on the performance of the LPSQ Function at PT.XXX include improved audit planning compliance and audit execution fulfillment, resulting in improvements in the audit reporting phase. The improvements obtained from using this application include easy presentation of audit results and more effective and efficient data delivery to audit leaders.